Design and Validity of Electronic Assessments to Assess Students' Critical Thinking Skills on Momentum and Impulse Materials - Diah Ayu Oktaviawati; Fatni Mufit (Jurnal Penelitian Pembelajaran Fisika, 2025)
Learners in the 21st century must have 4C skills, among these is the capacity for critical thought, especially in physics learning. Students' critical thinking abilities must be examined in order to prepare them for the twenty-first century. Assessment instruments that specifically assess students' critical thinking skills on momentum and impulse material are not yet available. So this research aims to develop a valid electronic assessment to assess students' critical thinking skills on momentum and impulse material. This research is development research (R&D) using the Plomp model. The data collection instruments used were interview sheets, self-evaluation sheets and validation sheets. The developed electronic assessment was validated by three validators. The electronic assessment had a high validity category in terms of material substance, learning design, visual communication, and software use, according to the validity analysis results. From the validation results with an average value of 0.92, it shows that the electronic assessment to assess students' critical thinking skills on momentum and impulse material is declared valid and feasible to use.